Pengaruh Kualitas Layanan, Harga, Desain Interior terhadap Keputusan Pembelian di Dkings Kafe Banyuwangi - Wilaga, Brian Ady; Hafidzi, Achmad Hasan; Izzudin, Ahmad (Lembaga Pengembangan Kinerja Dosen, 2025)
The culinary industry in Banyuwangi is experiencing significant growth with the emergence of many new cafes, leading to increasingly fierce competition among businesses. DKINGS Café, as one of the players in this industry, faces challenges in maintaining and increasing its customer base. This study aims to analyze the influence of service quality, price, and interior design on customer purchasing decisions at DKINGS Café Banyuwangi. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to DKINGS Café customers who had visited and made transactions more than twice. The sampling technique employed purposive sampling with a minimum number of 77 respondents, determined using the G*Power 3.1.9.7 software. Data analysis was conducted using multiple linear regression tests with the assistance of SPSS 27 software. The results of the study indicate that service quality does not have a significant effect on customers' purchasing decisions. In contrast, the price variable has a significant negative influence, meaning that the higher the price, the lower the customers’ purchasing decisions. Meanwhile, interior design is proven to have the strongest influence on purchasing decisions, where the more attractive the interior design, the higher the customers’ interest in making purchases.